2007
DOI: 10.1016/j.ejphar.2006.09.074
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine increases dopamine transporter function in rat striatum through a trafficking-independent mechanism

Abstract: In previous in vivo voltammetry studies, acute nicotine administration increased striatal dopamine clearance. The current study aimed to determine whether nicotine also increases [ 3 H]dopamine uptake across the time course of the previous voltammetry studies and whether dopamine transporter trafficking to the cell surface mediates the nicotine-induced augmentation of dopamine clearance in striatum. Rats were administered nicotine (0.32 mg/kg, s.c.); striatal synaptosomes were obtained 5, 10, 40 or 60 min late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 57 publications
1
32
3
Order By: Relevance
“…1) or K m (PFC: nicotine, 23.1 Ϯ 2.7 nM and saline, 21.0 Ϯ 1.9 nM; striatum: nicotine, 28.2 Ϯ 3.9 nM and saline, 26.0 Ϯ 4.5 nM). The current results from striatum with the low dose of nicotine are different from those reported previously (Middleton et al, 2007), in which nicotine (0.32 mg/kg s.c.) produced a small increase (23%) in V max in striatum (for explanation of the discrepancy in the results, see Discussion). In the current study, a higher dose of nicotine (0.8 mg/kg) also did not alter V max (Fig.…”
Section: Effect Of Acute Nicotine Administration On Synaptosomal [contrasting
confidence: 99%
See 1 more Smart Citation
“…1) or K m (PFC: nicotine, 23.1 Ϯ 2.7 nM and saline, 21.0 Ϯ 1.9 nM; striatum: nicotine, 28.2 Ϯ 3.9 nM and saline, 26.0 Ϯ 4.5 nM). The current results from striatum with the low dose of nicotine are different from those reported previously (Middleton et al, 2007), in which nicotine (0.32 mg/kg s.c.) produced a small increase (23%) in V max in striatum (for explanation of the discrepancy in the results, see Discussion). In the current study, a higher dose of nicotine (0.8 mg/kg) also did not alter V max (Fig.…”
Section: Effect Of Acute Nicotine Administration On Synaptosomal [contrasting
confidence: 99%
“…We reported recently that nicotine (0.3 mg/kg) produced a small, but significant, 23% increase in V max in rat striatum at 10 and 40 min after injection, which was not accompanied by an increase in cell surface DAT expression (Middleton et al, 2007). In the current study, no significant effect of this nicotine dose was observed during the 60-min period after injection; however, there was a tendency for a nicotine-induced increase (ϳ20%) in V max in striatum (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Nicotine increased dopamine clearance in the striatum (Hart and Ksir 1996;Middleton et al 2004Middleton et al , 2007a, and Middleton et al (2007a) further reported that nicotine increased the V max of rat striatal dopamine uptake in a manner independent of transporter trafficking. This effect on transporter function was transient in that it lasted less than 1 h. It is difficult to reconcile this finding with the present data because decreased synaptic dopamine would not be expected to exaggerate amphetamine response, unless it made more dopamine available for amphetamine-stimulated release or assisted the transport of amphetamine into the terminal.…”
Section: Discussionmentioning
confidence: 88%
“…Another issue relevant to this study is nicotine-, nornicotine-(produced by nicotine), and nicotine's metabolic intermediate, cotinineinduced release of DA through activation of nACh Rs. 50 We also explored a remarkable dose-and time-dependent shift of serum cotinine level in the experimental animals toward higher side without any detection in the controls as a result of the applied doses that resemble the human smoking scenario. 39 Serum cotinine is not detected in the control animals due to the nonavailability of the substance in the serum throughout the study period, suggesting toxic impact of the studied doses upon exposure, which corroborates several previous observations.…”
Section: Discussionmentioning
confidence: 99%